M. iKBAL'iN TEVHiD YORUMU: TEVHiD iNANCININ DiNAMiK YAPISI - Kaplan, İbrahim (Fırat University, 2007)
lqbal's thinking system is founded upon the Tawhced belief. In his opinion, God is single, and a unique personality, an absolute Ego. According to lqbal, Koran's view of divinity, universe, man and society has entirely a dynamic structure. In his interpretation of the Tawheed, Iqbal puts emphasis upon God's attributes such as knowledge, will and creation, and the n he discusses these attributes in the context of man' s actions in connection with man's freedom and destiny. In his philosophy, God's existence, his uniqueness, perfectness; and dynamism keeps an irnportanr conceptua! place. God's attribiıtes in his philosophy take on a shape around his idea of a dynamic universe, a dynamic understanding of divinity, and the idea of God's indivi.duality. In order to eliminate the misconceptions wi.th regard to the Ta\vheed understandi.ng and to make society acquire a dynamic world view agai.n, Iqbal seems to have reformulated the understandi.ng of di.vinity mostly ina loyal attitude to Koran.
Keywords: Religious Studies; Din Araştırmaları